2021
DOI: 10.14710/ijred.2021.38238
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Wind Energy and Design Implications on Wind Farms in Saudi Arabia

Abstract: Climate change and natural resource depletion are likely to affect the future economic development of a country. The generation of power from oil and gas is among the major causes of reserves depletion and global warming. However, renewable energy is also deemed a clean and green choice for power generation to promote sustainability in engineering. The coastal lines of the Kingdom of Saudi Arabia (KSA) are widely extended, and wind energy appears to be a viable alternative to traditional sources, which needs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…They also found that a decrease in total primary energy supply in oil-rich nations leads to an increase in energy supply on the international market, subsequently alleviating the global pressure on oil and gas prices. Also, Naqash et al (2021) researched the potential of wind energy along the Red Sea coast of the oil-rich Kingdom of Saudi Arabia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also found that a decrease in total primary energy supply in oil-rich nations leads to an increase in energy supply on the international market, subsequently alleviating the global pressure on oil and gas prices. Also, Naqash et al (2021) researched the potential of wind energy along the Red Sea coast of the oil-rich Kingdom of Saudi Arabia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study's goals are to minimize water loss due to leaks, provide useful data to the main server where bills are calculated based on water usage, and create a dashboard of the monitoring system that displays current water usage, forecasts future usage, and provides recommendations to each company on how to use water efficiently. The existing infrastructure of the water supply distribution in the KSA, the centralized control room for monitoring and controlling the supply of water to various companies, the monitoring and control of water pressure in pipes leading from a seawater plant to consumers, cooperative solutions to control leakage in the network of pipes leading from a desalinated plant to consumers and whether consumers receive suitable drinking water are some of the research questions this study looks into [7].…”
Section: Introductionmentioning
confidence: 99%
“…The world is experiencing an increase in the use of renewable sources of energy to restrain the effects of global climate change by decreasing the emission of CO2 and increasing the security of the energy supply by reducing the proportion of use of fossil sources of energy especially with rising oil price (Lakatos et al, 2011;Rehman et al, 2023). The most actively developing areas of renewables are solar and wind generation (Li et al, 2022;Roga et al, 2022;Naqash et al, 2021). However, wind power is one of the fastest-growing renewables segments due to its ability to generate large amounts of energy at competitive costs (Chaudhuri et al, 2022).…”
Section: Introductionmentioning
confidence: 99%